2021
DOI: 10.7717/peerj.10647
|View full text |Cite
|
Sign up to set email alerts
|

Refining the marine reptile turnover at the Early–Middle Jurassic transition

Abstract: Even though a handful of long-lived reptilian clades dominated Mesozoic marine ecosystems, several biotic turnovers drastically changed the taxonomic composition of these communities. A seemingly slow paced, within-geological period turnover took place across the Early–Middle Jurassic transition. This turnover saw the demise of early neoichthyosaurians, rhomaleosaurid plesiosaurians and early plesiosauroids in favour of ophthalmosaurid ichthyosaurians and cryptoclidid and pliosaurid plesiosaurians, clades that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 173 publications
2
28
0
7
Order By: Relevance
“…The specimen MNHNL TU885 was found at Schouweiler near Bascharage and Sanem, Grand Duchy of Luxembourg (Fig. 1B), a region well known for its marine reptile fossil richness (Streitz, 1983;Godefroit, 1994;Vincent et al, 2017;Johnson et al, 2019;Fischer et al, 2021).…”
Section: Spatiotemporal Setting Of Mnhnl Tu885mentioning
confidence: 99%
“…The specimen MNHNL TU885 was found at Schouweiler near Bascharage and Sanem, Grand Duchy of Luxembourg (Fig. 1B), a region well known for its marine reptile fossil richness (Streitz, 1983;Godefroit, 1994;Vincent et al, 2017;Johnson et al, 2019;Fischer et al, 2021).…”
Section: Spatiotemporal Setting Of Mnhnl Tu885mentioning
confidence: 99%
“…A novelty of the Pliensbachian is to record the slightly more derived taxon Hauffiopteryx (Maxwell and Cortés, 2020). Thanks to the Cloche d'Or locality, all stages of the Early Jurassic are now known to contain large early neoichthyosaurians (with centra diameter > 10 cm) in many places of the European Archipelago (Godefroit, 1993;McGowan, 1996;Martin et al, 2012;Maxwell and Vincent, 2015;Fischer et al, 2021). By contrast, baracromians dominate ichthyosaurian assemblages in the European Archipelago by the early Toarcian with the ubiquitous presence of multiple species of Stenopterygius (Huene, 1931b;Hauff, 1953;Godefroit, 1994;Maisch, 2010;Maxwell, 2012;Dick et al, 2016) and are the only ichthyosaurians found after the Bajocian, with the exception of Malawania anachronus (Fernández, 1994;Fischer et al, 2013Fischer et al, , 2021.…”
Section: Possible Surangular Vertebratamentioning
confidence: 99%
“…Thanks to the Cloche d'Or locality, all stages of the Early Jurassic are now known to contain large early neoichthyosaurians (with centra diameter > 10 cm) in many places of the European Archipelago (Godefroit, 1993;McGowan, 1996;Martin et al, 2012;Maxwell and Vincent, 2015;Fischer et al, 2021). By contrast, baracromians dominate ichthyosaurian assemblages in the European Archipelago by the early Toarcian with the ubiquitous presence of multiple species of Stenopterygius (Huene, 1931b;Hauff, 1953;Godefroit, 1994;Maisch, 2010;Maxwell, 2012;Dick et al, 2016) and are the only ichthyosaurians found after the Bajocian, with the exception of Malawania anachronus (Fernández, 1994;Fischer et al, 2013Fischer et al, , 2021. The Pliensbachian gap in the fossil record of ichthyosaurians might contain this change of dominance; in any case, these remains further highlight the importance of the Luxembourg-Trier basin deposits in understanding the diversity dynamics of Jurassic marine reptiles.…”
Section: Possible Surangular Vertebratamentioning
confidence: 99%
See 1 more Smart Citation
“…Four lithostratigraphic members are outcropping at the different levels of the quarry (Fig. 5d), notably the 'Calcaire d'Audun-le-Tiche' with coral patch reefs (Lucius 1945;Hary 1970;Geister 1984Geister , 1986Lathuilière 2000a,b) and the 'Marnes sableuses d'Audun-le-Tiche' with namely large cephalopods (Weis 2006), fish teeth (Delsate & Felten 2015;Popov et al 2019), echinids (Thuy 2003(Thuy , 2010b, and marine reptile remains (Fischer et al 2021), as well as a single dinosaur osteoderm (Delsate et al 2018). The site has high educational potential and access is possible to professionals, under certain conditions and with a special permit.…”
Section: Calcaire De Rumelange Unit (Lower Bajocian)mentioning
confidence: 99%